Eradication Of Poverty And Welfare In An Islamic Perspective - Nanang Yusroni; Mochamad Purnomo; Umar Chadhiq; Nurul Komaryatin (Fakultas Ekonomika dan Bisnis Universitas Selamat Sri, 2022)
Islam is a religion, and religion is closely linked tobelief. Furthermore beliefs are emotional, andtherefore need islamic and non-Muslim relations tobe well regulated. The difference between rich andpoor always brings chaos in society and toovercome it, the verses of the Qur'an also concernthe relationship of rich and poor. The economicseverity of our country over the years has led topoverty, which has swelled and increased. Swellsand rising poverty are evident with the increasingnumber of unemployment, Unemployment isincreasingly large children and adolescents out ofschool, homeless, low quality, violent behavior andefficacy and imperviousness. That is how it is,poverty has attracted to disbelief, low temperamentand criminality that harms society. Thus, poverty isone of those social problems that can be viewed asanother source of social problems.